Inflammatory profile of incident cases of late-onset compared with young-onset rheumatoid arthritis: A nested cohort study - Mena-Vázquez, Natalia; Lisbona-Montañez, Jose Manuel; Redondo-Rodriguez, Rocío; Mucientes, Arkaitz; Manrique-Arija, Sara; Rioja, José; Garcia-Studer, Aimara; Ortiz-Márquez, Fernando; Cano-García, Laura; Fernández-Nebro, Antonio (Frontiers in Medicine, 2022)
Objectives To describe the characteristics of patients between late-onset rheumatoid arthritis (LORA) with young-onset (YORA), and analyze their association with cumulative inflammatory burden. Methods We performed a nested cohort study in a prospective cohort comprising 110 patients with rheumatoid arthritis (RA) and 110 age- and sex-matched controls. The main variable was cumulative inflammatory activity according to the 28-joint Disease Activity Score with erythrocyte sedimentation rate (DAS28-ESR). High activity was defined as DAS28 ≥ 3.2 and low activity as DAS28 < 3.2. The other variables recorded were inflammatory cytokines, physical function, and comorbid conditions. Two multivariate models were run to identify factors associated with cumulative inflammatory activity. Results A total of 22/110 patients (20%) met the criteria for LORA (≥ 60 years). Patients with LORA more frequently had comorbid conditions than patients with YORA and controls. Compared with YORA patients, more LORA patients had cumulative high inflammatory activity from onset [13 (59%) vs. 28 (31%); p = 0.018] and high values for CRP (p = 0.039) and IL-6 (p = 0.045). Cumulative high inflammatory activity in patients with RA was associated with LORA [OR (95% CI) 4.69 (1.49–10.71); p = 0.008], smoking [OR (95% CI) 2.07 (1.13–3.78); p = 0.017], anti–citrullinated peptide antibody [OR (95% CI) 3.24 (1.15–9.13); p = 0.025], average Health Assessment Questionnaire (HAQ) score [OR (95% CI) 2.09 (1.03–14.23); p = 0.034], and physical activity [OR (95% CI) 0.99 (0.99–0.99); p = 0.010]. The second model revealed similar associations with inflammatory activity in patients with LORA. Conclusion Control of inflammation after diagnosis is poorer and comorbidity more frequent in patients with LORA than in YORA patients and healthy controls.